A Study of the Concentration of Cadmium Element in Calf Carcasses in Different Areas in the Syrian Coast - Gheiath H. Soliman; Arwana, Abed El-Aziz (Latakia University Journal -Biological Sciences Series, 2013)
A random sample of 240 )80 muscles, 80 kidneys, and 80 livers) were collected from 80 calf carcasses (1-3 years old) in Lattakia and Tartous Governorates, and Jableh and Safita Regions. The samples were examined in order to detect contamination by Cadmium Element using Atomic Absorption Spectrometry (AAS). The results showed that the concentration of cadmium in the calves’ kidneys, livers, and muscles in Lattakia is (0.5202, 0.427 and 0.0283mg/kg) respectively, (0.5955, 0.398, and 0.0235mg/kg) in Jableh, (0.699, 0.347, and 0.0139mg/kg) in Tartous, and (0.684, 0.311, and 0.0135mg/kg) in Safita. Results also showed an increase in the contamination level by cadmium in the kidneys, livers, and muscles. The contamination level was more in Lattakia and Tartous than in Jableh and Safita. Muscle, liver and kidney samples in all regions were within the permissible limits according to the Syrian standard Specifications.